Association Between Dietary Inflammatory Index Scores and Hemoglobin Levels Among Pregnant Women in Asahan Regency: A Cross-Sectional Study - Fenny Anggreany Nasution; Ninik Rustanti; Ahmad Syauqy (Media Publikasi Cendekia Indonesia, 2026)
Anemia during pregnancy remains a major public health concern and is influenced not only by iron intake but also by dietary patterns that modulate inflammatory processes. The Dietary Inflammatory Index (DII) is a validated tool used to quantify the inflammatory potential of an individual’s diet and may be associated with hemoglobin (Hb) levels. This study aimed to examine the association between DII scores and hemoglobin levels among pregnant women in Asahan Regency, Indonesia. A cross-sectional study was conducted among 170 pregnant women selected through purposive sampling. Dietary intake was assessed using a semi-quantitative food frequency questionnaire (SQ-FFQ), and DII scores were calculated using 28 out of 45 validated dietary parameters. Hemoglobin levels were obtained from laboratory measurements. Normality testing using the Kolmogorov–Smirnov test showed that both variables were not normally distributed; therefore, Spearman’s correlation analysis was applied. The median hemoglobin level was 11.45 g/dL, while the median DII score was –3.94, indicating a predominantly anti-inflammatory dietary pattern. Spearman’s correlation analysis revealed a strong and significant negative association between DII score and hemoglobin level (ρ = –0.536; p < 0.001), indicating that higher pro-inflammatory dietary potential was associated with lower hemoglobin concentrations. Multivariable analysis adjusting for maternal age, gestational age, parity, and mid-upper arm circumference (MUAC) confirmed that DII score remained an independent predictor of hemoglobin level. These findings highlight the importance of promoting anti-inflammatory dietary patterns during pregnancy to support optimal hemoglobin status and reduce the risk of anemia. Incorporating dietary inflammatory assessment into antenatal nutrition programs may strengthen anemia prevention strategies and improve maternal health outcomes.